Linking Exercise Self-Efficacy to Perceived Wellness: Implications for Student Well-Being in Higher Education - Sameon, Michael Andrei; Villarojo, Bryan Paul (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to examine the relationship between exercise self-efficacy and perceived wellness among Filipino college freshmen in Davao del Norte within the context of curriculum evaluation in physical education. It sought to assess students’ levels of exercise self-efficacy and perceived wellness as indicators of holistic development and to explore how these constructs inform program evaluation and learning outcomes in PE. Methodology: The study used a quantitative-correlational research design involving 298 college freshmen enrolled in PE 1 – Movement Enhancement during the academic year 2023–2024. Data were collected using three adapted research instruments measuring exercise self-efficacy and perceived wellness. Descriptive statistics (mean) and Pearson product-moment correlation were used for data analysis. Main Findings: The results showed that students had a moderate level of exercise self-efficacy and a high level of perceived wellness. A statistically significant positive relationship was found between exercise self-efficacy and perceived wellness, indicating that students with higher confidence in performing exercise tend to have better overall wellness. Novelty/Originality of this study: This study uniquely evaluates the relationship between exercise self-efficacy and perceived wellness among Filipino college freshmen within an educational evaluation framework. By integrating the CIPP and Kirkpatrick models, it provides new insights into how exercise confidence contributes to holistic well-being.